Investigation on ultrasonic assisted friction stir welding of aluminum/steel dissimilar alloys - Hong Kairong (De Gruyter, 2021)
The extensive use of light metal material such as aluminum has brought about problems in its joining with steel. However, the weak metallurgical bonding between the dissimilar materials and the formation of hard and brittle intermetallic compounds (IMCs) lead to unsatisfactory joint strength. Aiming at achieving high-quality joining of aluminum and steel, 6061-T6 aluminum and 301L steel alloys were lap joined by ultrasonic assisted friction stir lap welding (UaFSLW) in this study. The UaFSLW joints were well formed with uniform flashes and even arc lines. The strong plastic flow of the aluminum material driven by the dual effects of mechanical stirring and ultrasonic vibration inhibited the excessive growth of the Al–Fe IMCs at the lap interface. Thanks to the enhanced metallurgical bonding and the effective control of the layer thickness of IMCs, the tensile load of the UaFSLW joint under 1,800 rpm reached 16.5 kN, which was an increase of 27.9% compared to that of the conventional FSLW joint.